Two newly discovered Grateloupia (Halymeniaceae, Rhodophyta) species on aquaculture rafts on the west coast of South Africa, including the widely introduced Grateloupia turuturu. Issue 6 (1st November 2016) - Bolton, John J.; De Clerck, Olivier; Francis, Caitlynne M.; Siyanga-Tembo, Fridah; Anderson, Robert J.
Abstract: Compared with other world regions, very few species of marine macroalgae have been demonstrated to be recent introductions into South Africa. Collections of red seaweeds growing on ropes on an oyster farm in Saldanha Bay on the west coast of South Africa included two species of Grateloupia . The most abundant one is foliose, and has identical rbc L and cox 1 sequences to that of Grateloupia turuturu, indigenous to Japan/Korea but introduced into many world regions. The other species is finely branched and presumably also an introduction, being closest in rbc L sequence to G. carnosa from Japan but not identical. Our findings highlight the continuous risk imposed by the translocation of oysters for mariculture purposes to spread and introduce non-native and potentially invasive species worldwide. In addition, our inability to identify the second species, despite its sister relationship to a species from the Western Pacific Ocean, calls for the establishment of a reference DNA-barcode library of seaweeds from the temperate Western Pacific Ocean to facilitate the early detection of introduced and potentially invasive seaweeds. South Africa now has three foliose and two filamentous species of Grateloupia sensu lato . Although the newly introduced species have not been recorded outside the Saldanha Bay area so far, continuous monitoring is advised to document the future spread of the species and their effects on native coastal ecosystems.